2012
DOI: 10.1111/j.1365-294x.2012.05613.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of genetic differentiation between monarch butterflies with divergent migration destinations

Abstract: Monarch butterflies are best known for their spectacular annual migration from eastern North America to Mexico. Monarchs also occur in the North American states west of the Rocky Mountains, from where they fly shorter distances to the California Coast. Whether eastern and western North American monarchs form one genetic population or are genetically differentiated remains hotly debated, and resolution of this debate is essential to understand monarch migration patterns and to protect this iconic insect species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 57 publications
6
89
0
Order By: Relevance
“…Owing to the panmictic nature of the population in North America, our results provide a new outlook on monarch butterfly migration pathways. Results here also indicate that different migration strategies, such as the use of different overwintering sites or the presence of non-migratory behaviour, can be maintained between populations despite high levels of gene flow [38], as also seen in the admixed populations of migratory and sedentary groups of broad-tailed hummingbirds in North America [59]. A similar lack of neutral genetic differentiation has been observed in other highly mobile, migrating species, such as hoverflies with different overwintering strategies in France [60] and blackcaps with different migratory behaviours and destinations in Europe [61].…”
Section: (B) Implicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Owing to the panmictic nature of the population in North America, our results provide a new outlook on monarch butterfly migration pathways. Results here also indicate that different migration strategies, such as the use of different overwintering sites or the presence of non-migratory behaviour, can be maintained between populations despite high levels of gene flow [38], as also seen in the admixed populations of migratory and sedentary groups of broad-tailed hummingbirds in North America [59]. A similar lack of neutral genetic differentiation has been observed in other highly mobile, migrating species, such as hoverflies with different overwintering strategies in France [60] and blackcaps with different migratory behaviours and destinations in Europe [61].…”
Section: (B) Implicationsmentioning
confidence: 80%
“…From North American migratory monarchs, we included samples from one fall migratory stopover site in north Florida (St Marks: 100 monarchs), two California overwintering sites (Pismo Beach and Santa Barbara: 100 monarchs) and two Mexico overwintering sites (Cerro Pelon and Sierra Chincua: 27 monarchs). We refer to the monarchs sampled from the eastern and western United States as the USA sample from hereon because despite overwintering in different locations, eastern and western North American monarchs are genetically indistinguishable on the basis of microsatellites [38]. We also included samples from non-migratory New World monarchs inhabiting South Florida, southern North America (Costa Rica and Belize), Caribbean and Atlantic islands (Puerto Rico and Bermuda) and South America (Ecuador and Aruba).…”
Section: Materials and Methods (A) Monarch Field Collectionsmentioning
confidence: 99%
“…Leaf tissue analysis The presence of clothianidin was tested in milkweed (Asclepias syriaca) plants that were a mean (SEM) 1.47±0.39 m from maize fields in Brookings County, SD, soon after maize planting (June 20, 2014; plants were 5-15 cm tall; n=8 sites), and when monarch populations were most abundant (July 25, 2014; n=10 sites; Lyons et al 2012). The late planting date in our area was the result of a very wet spring.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…In general, monarchs east of the Rocky Mountains migrate to Mexico while monarchs west of the Rocky Mountains migrate to locations along the Pacific coast of California (Urquhart and Urquhart 1977), aggregating in groves of Monterey pine (Pinus radiata), Monterey cypress (Cupressus macrocarpa), and blue gum (Eucalyptus globulus) (Weiss et al 1991). Genetic studies have suggested that these populations are not distinct (Brower and Malcolm 1991;Lyons et al 2012;Zhan et al 2014), and some western monarchs potentially overwinter in Mexico (Dingle et al 2005;Morris et al 2015). Both populations depend on host plants in the genus Asclepias, the milkweeds.…”
Section: Introductionmentioning
confidence: 99%